Studi Eksperimentasi Posisi Pendingin Termoelektrik pada Kotak Pendingin terhadap Kinerja Sistem Pendingin bertenaga Panel Surya - Rifky; Eki Hadi Setiawan; Delvis Agusman; Mohammad Mujirudin; Arry Avorizano (METALIK : Jurnal Manufaktur, Energi, Material Teknik, 2025)
Solar cells are a powerful technology to convert solar energy into electrical energy directly, while thermoelectrics can convert electrical energy (potential difference) into heat energy (temperature difference). The combined solar cell and thermoelectric system is used as an air conditioner. The research was conducted by making a cooling system in the form of a cooling box with a cooling source on the roof side and wall side. The cooling source in this study is a thermoelectric cooling system consisting of a series of thermoelectric modules. The purpose of this study is to find that the position of the TEC affects the cooling results in the cooling box and determine the lowest temperature and performance of the cooling system in the cooling box. The method used is an experimental method with the model is a cooler box with cooler box dimensions: 520mm x 370mm x 440mm. Solar cells as electrical energy suppliers are placed in the presence of sunlight throughout the day and the output power from solar cells is distributed to the thermoelectric cooling system in series. so that thermal energy changes take place on its sides. The cold side of the thermoelectric will absorb heat from inside the cooling box, while the hot side of the thermoelectric will release heat to the environment outside the cooling box. The results showed that the positioning of the thermoelectric cooler on the roof side and the wall side of the cooler box affected the heat transfer and temperature achievement in the center of the cooler box. The average center room temperature achieved by the cooler on the roof side is 23.70 ℃ and 24.75 ℃ on the wall side. While the coefficient of performance of the cooling system in the cooler box with thermoelectric cooler on the roof side amounted to 2.17 and in the thermoelectric cooler on the wall side amounted to 1.8.